YOSHIHIDE SUGA POLICY DALAM MELANJUTKAN ABENOMICS DI KAWASAN ASIA TIMUR DAN TENGGARA - Ade Priangani (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2021)
This article describes a problem regarding abenomics made by Shinzo Abe as the basis of Japan's domestic political economy and foreign policy which began in 2012. However, after Shinzo Abe's emergence as PM of Japan and replaced by Yoshihide Suga, Suga continued abenomics with the aim of improving and stabilization of both Japan Domestic and Asia Pacific region, stimulaneously with RCEP which was signed in November 2020. The author takes the concept of Foreign Policy in which Japan improves its leadership strategy in balancing China's influence on the East Asian Region and ASEAN. The assumption of the leadership strategy is that the state has the capability of power but does not engage in conflictualism with other countries, so that it cooperates with a sense of competitiveness of a country. The result of the analysis shows that Japan sees an opportunity with the RCEP. Previously Japan did not focus on RCEP as part of Abenomics but rather on the CPTPP. However, because RCEP can encourage the export of Japanese products or commodities, RCEP is the most important part for Japan in the economy on free economy in Asia Pacific region. However, the challenge from Japan is that China still has a strong influence on ASEAN and RCEP has low trade liberalization. So that India left RCEP because of concerns that India's local products could not compete with other countries, especially China, with products that were cheap and accessible to the public. In addition, ASEAN sees China as no longer a threat because it sees China as a potential market for ASEAN. The impact for Indonesia is to get the maximum benefit from the Sino-Japanese competition, one of which is the joint project of the Jakarta-Bandung Fast Train as an interest of Indonesia which implements a Free Active Foreign Policy.